Innovations in Eye Care: Sport Vision - Erickson, Graham (Canadian Journal of Optometry, 2017)
Optometry has a long tradition of providing vision care services to optimize daily function. While this has often focused on academic and occupational performance, sports performance is another important area where vision plays a critical role. Athletes, trainers and coaches have recognized that excellent vision is an important aspect of performance [...]